Nontraumatic Spondylolisthesis of the Axis with Cervical Kyphosis - Shuhei Mizobuchi; Nobuaki Tadokoro; Shogo Takaya; Katsuhito Kiyasu; Ryuichi Takemasa; Masahiko Ikeuchi (Case Reports in Orthopedics)
This study aimed at presenting a rare nontraumatic spondylolisthesis of the axis and considering its possible cause. Traumatic spondylolisthesis of the axis, called hangman’s fracture, frequently occurs as a high-energy trauma. However, nontraumatic spondylolisthesis of the axis is quite rare, and relevant literature on this condition is scarce. We reported a case of a 49-year-old man who had spondylolisthesis of the axis without experiencing a traumatic episode. Plain radiograph and CT image showed 7.0 mm anterolisthesis of the axis. Both C2 and C3 facet joints positioned asymmetrically, and the unilateral side oriented coronally, which was less resistant to rotational motion. These facet joint abnormalities could cause segmental instability and spondylolisthesis of the axis. Due to the resultant myelopathy, the slip with cord compression was surgically corrected by posterior decompression with instrumented fusion.